Multi-Photon Quantum Information Science and Technology in Integrated Optics - Matthews, Jonathan C.F.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Photons are an attractive option for testing fundamental quantum physics and developing new quantum-enhanced technology, including highly advanced computers and simulators, as well as precision sensing beyond shot-noise. Traditionally, bulk optical components have been bolted onto optical benches to realize metre-scale quantum circuits. However this approach is ultimately proving unwieldy for increasing the complexity and for scaling up to practical quantum technologies based on photons. The work presented here demonstrates a series of quantum photonic devices based on waveguide circuits embedded in miniature monolithic chips. This represents a paradigm shift in the underlying architecture of quantum optics and provides key building blocks for all-optical and hybrid quantum technologies.
Background and Methods -- The Hong-Ou-Mandel effect in a waveguide directional coupler -- Multi directional-coupler circuit for quantum logic -- Quantum interference in a waveguide interferometer -- Heralded NOON state generation in waveguide -- Two photon quantum walks -- Simulating arbitrary quantum statistics with entangled photons.
Keywords: Physics; Physics; Quantum Optics; Optics, Optoelectronics, Plasmonics and Optical Devices; Nanoscale Science and Technology